Physical Fitness Analysis of Junior High School Students Phase D Using Indonesian Student Fitness Test Instruments - Saputra, Hendri Jagat; Muhaimin, Ali; Syarifoeddin, Elya Wibawa (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2026)
This study aims to describe the level of physical fitness of grade VIII students and compare the achievement of fitness components based on gender using the Indonesian Student Fitness Test (TKSI) Phase D. The use of TKSI Phase D is a practical contribution to this study because it provides a standardized fitness mapping, contextual, and can be directly used by PJOK teachers as a basis for student coaching. The research uses a descriptive-comparative quantitative approach with a survey method. The sample consisted of 37 students in grade VIII-1, including 17 male students and 20 female students, who were selected through purposive sampling techniques based on active participation, consistency of attendance, and willingness to participate in the entire series of tests. TKSI Phase D instruments include hand and eye coordination test, sit-up test, standing broad jump test, T-test, and beep test. Data were analyzed using frequency distribution, percentages, descriptive statistics, and independent t-test samples. The results showed that the overall physical fitness level of students was in the medium category, with 10 students in the good category, 15 students in the medium category, 11 students in the low category, and 1 student in the low category. Based on gender, dominant male students are in the medium category, while dominant female students are in the less category. The results of the differential test showed that male students had significantly better performance in all components of TKSI, namely muscle endurance, leg explosiveness, agility, cardiorespiratory endurance, and eye-hand coordination. These findings confirm that TKSI Phase D can serve as an initial diagnostic basis for designing more adaptive fitness interventions in local schools on an ongoing basis. This study concludes that students' physical fitness still requires targeted coaching through data-driven PJOK learning, especially for students with low fitness categories. Keywords: Physical Fitness; TKSI Phase D; Junior High School Students; Physical Education; Student Fitness